Gut neurotoxin p-cresol induces differential expression of GLUN2B and GLUN2A subunits of the NMDA receptor in the hippocampus and nucleus accumbens in healthy and audiogenic seizure-prone rats - Gigi Tevzadze; Elene Zhuravliova; Tamar Barbakadze; Lali Shanshiashvili; Davit Dzneladze; Zaqaria Nanobashvili; Tamar Lordkipanidze; David Mikeladze (AIMS Neuroscience, 2020)
Mislocalization and abnormal expression of N-methyl-D-aspartate glutamate receptor (NMDAR) subunits is observed in several brain disorders and pathological conditions. Recently, we have shown that intraperitoneal injection of the gut neurotoxin p-cresol induces autism-like behavior and accelerates seizure reactions in healthy and epilepsy-prone rats, respectively. In this study, we evaluated the expression of GLUN2B and GLUN2A NMDAR subunits, and assessed the activity of cAMP-response element binding protein (CREB) and Rac1 in the hippocampi and nucleus accumbens of healthy and epilepsy-prone rats following p-cresol administration. We have found that subchronic intraperitoneal injection of p-cresol induced differential expression of GLUN2B and GLUN2A between the two brain regions, and altered the GLUN2B/GLUN2A ratio, in rats in both groups. Moreover, p-cresol impaired CREB phosphorylation in both brain structures and stimulated Rac activity in the hippocampus. These data indicate that p-cresol differently modulates the expression of NMDAR subunits in the nucleus accumbens and hippocampi of healthy and epilepsy- prone rats. We propose that these differences are due to the specificity of interactions between dopaminergic and glutamatergic pathways in these structures.